Physician‐anatomists of Italy in Şānīzāde Mehmed Atāullah Efendi's work Mir'āt al‐Abdān (mirror of bodies). Issue 6 (19th April 2014) - Aciduman, Ahmet; Arda, Berna
<x xml:space="preserve">Abstract</x> Şānīzāde Mehmed Atāullah Efendi was a pioneer in the history of Turkish medical education with his work Ḫamse‐i Şānīzāde (Five Works of Şānīzāde). The first of these works, Mir'āt al‐abdān fī taşrīh‐i a'ḍāi'l‐insān (Mirror of the Bodies in the Dissection of the Members of the Human Body), concerns anatomy and was written in 1816. Şānīzāde's Mir'āt al‐abdān is an important milestone in the teaching of anatomy in the Ottoman Empire and was also the first book on anatomy both written in a modern manner and printed in the Ottoman Empire. This paper is based on investigation of a printed copy of Mir'āt al‐Abdān in the library of the History of Medicine and Ethics Department, Ankara University Faculty of Medicine. The main text and explanations were transliterated into the contemporary Turkish alphabet. The names of European physicians and their eponyms in the main text and in the explanations of illustrations were identified and evaluated. The names of European masters of anatomy in Şānīzāde are mentioned either in the text or in plate explanations. These names and plates indicate well‐known physicians and masters of anatomy whose works were examined and quoted by Şānīzāde. The references in Şānīzāde's book and presented in this study relate to Italian physician‐anatomists such as Bartolomeo Eustachi, Gabriele Fallopio, Costanzo Varolio and to others, such as Andreas Vesalius and Adriaan van den Spiegel, who were also Padua‐educated but not Italian. Clin. Anat. 27:808–814, 2014. © 2014 Wiley Periodicals, Inc.